Impact of adjuvant chemotherapy for stage I ovarian carcinoma with intraoperative tumor capsule rupture. Issue 3 (20th October 2014) - Shimizu, Dai; Sato, Naoki; Sato, Toshiharu; Makino, Kenichi; Kito, Masahiko; Shirasawa, Hiromitsu; Kumagai, Jin; Terada, Yukihiro
Abstract Aim Adjuvant chemotherapy is generally recommended for early stage epithelial ovarian cancer. However, it remains uncertain which histological subtypes and substages of stage I disease should receive adjuvant chemotherapy. The objective of this study is to determine the impact of chemotherapy among stage I epithelial ovarian cancer. Material and Methods Of the 267 patients with stage I epithelial ovarian cancer analyzed in this study, 152 patients received adjuvant chemotherapy (AC‐positive group) and 115 patients did not (AC‐negative group). Survival analysis was retrospectively performed to determine the effectiveness of adjuvant chemotherapy in stage I epithelial ovarian cancer patients. Results Recurrence was observed in 14 patients in the AC‐negative group and 20 patients in the AC‐positive group. There were no statistically significant differences in disease‐free survival (DFS) and overall survival between the two groups. In stage IA and IB patients, there was no statistically significant difference in DFS and overall survival based on adjuvant chemotherapy status. However, in patients with intraoperative tumor capsule rupture, the AC‐positive group had significantly better DFS than the AC‐negative group (P = 0.01). Patients with clear cell carcinoma who received adjuvant chemotherapy had better DFS than patients who did not (P = 0.004). Conclusions Adjuvant chemotherapy may not be necessary for patients with stage IA or IB epithelial ovarian cancer, but may be beneficial for clear cell carcinoma patients with intraoperative tumor rupture.